2014
DOI: 10.4062/biomolther.2014.081
|View full text |Cite
|
Sign up to set email alerts
|

Novel Suppressive Effects of Ketotifen on Migration and Invasion of MDA-MB-231 and HT-1080 Cancer Cells

Abstract: The high mortality rates associated with cancer reflect the metastatic spread of tumor cells from the site of their origin. Metastasis, in fact, is the cause of 90% of cancer deaths. Therefore, considerable effort is being made to inhibit metastasis. In the present study, we screened ketotifen for anti-migratory and anti-invasive activities against MDA-MB-231 breast cancer and HT-1080 fibrosarcoma cancer cells. Cancer cell migration and invasion were measured using multi-well chambers. Additionally, western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…At 10 mM of ketotifen, the exosome released by HeLa, MCF7 and BT549 cells decreased by 70%, 45% and 30%, respectively. Surprisingly, the effect of ketotifen on exosome increases the sensitivity of cancer cells to doxorubicin and also suppresses the progression of cancer cells 49,72 . As ketotifen was reported to block calcium influx into cells, and It is shown that exosome release was regulated by calcium-dependent mechanisms, and inhibitors of calcium entry into the cells reduce exosome release 73,74 .…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…At 10 mM of ketotifen, the exosome released by HeLa, MCF7 and BT549 cells decreased by 70%, 45% and 30%, respectively. Surprisingly, the effect of ketotifen on exosome increases the sensitivity of cancer cells to doxorubicin and also suppresses the progression of cancer cells 49,72 . As ketotifen was reported to block calcium influx into cells, and It is shown that exosome release was regulated by calcium-dependent mechanisms, and inhibitors of calcium entry into the cells reduce exosome release 73,74 .…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…This effect is believed to be mediated by a block of calcium entry into the cells. 2,5,14 In the present study, we investigated whether ketotifen would alter exosome release from cancer cells and whether this activity may enhance the anti-tumor effects of doxorubicin in three different cancer model cell lines, namely HeLa (in vitro model for cervix carcinoma), MCF7 (in vitro model for breast cancer) and BT549 (in vitro model for breast cancer). The ultimate goal is to open the door for developing pharmacological agents targeting exosome release and their role in supporting the growth of cancer cells and their resistance to cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Two other antihistamines, clemastine and desloratadine, induced T-cell lymphoma cell apoptosis that are involved in downregulating signal transducer and activator of transcription 3 (STAT3) and cellular myelocytomatosis (c-Myc) activities [ 10 ]. Moreover, ketotifen decreased the cell migration and invasion of breast cancer and fibrosarcoma cells, and the underlying mechanisms were associated with inhibition of cell division cycle 42 (Cdc42), Rho, Rac, and matrix metalloproteinase (MMP)-9 expressions [ 11 ]. Loratadin, a long-acting, non-sedating antihistamine drug enhanced the radiation sensitivity and then disrupted the cell cycle progression of human colon carcinoma cells [ 12 ].…”
Section: Introductionmentioning
confidence: 99%